Impact of COVID-19 Pandemic on Money Market Liquidity in Bangladesh (Social Science Review, 2023)
Recently, there has been a significant interest among the researchers to investigate the impact of Covid-19 pandemic on different economies of the world. While most of those studies focus on mac ro-economic perspective and are based on the western and developed economies, this study aims to investigate the impact of the pandemic on the money market of a developing economy (e.g., Bangladesh), the series of steps undertaken by the policy makers of the country and the consequences of those interventions on the liquidity of the money market based on the data from July 2018 to June 2021. Our analysis shows that the central bank of the country, Bangladesh Bank, without any delay implemented an expansionary monetary policy to ease the financial stress caused by the pandemic. We identified the policies adopted by the authorities included injecting liquidity, reducing interest rates, easing inflows of inward remittance, reducing CRR requirements, increasing Repo facilities at lower rates, reducing Annual Development Programme (ADP) implementation, borrowing from foreign channels instead of domestic markets etc. We also discussed the consequences (e.g., the record Foreign Exchange Reserve, a huge inflow of BDT liquidity in the market etc.) of the series of those interventions and outline the theoretical implications drawing on the findings.Social Science Review, Vol. 39(1), June 2022 Page 179-198